Effectiveness of Sun Protection in Outdoor Athletes in the Prevention of Skin Cancer – A Literature Review - Tabian, Alicja; Kozłowska, Paulina; Smęt, Jakub; Chojnacka, Aleksandra; Borawski, Jacek; Burdon-Sajnóg, Julia; Szymona-Kuciewicz, Zofia; Bartela, Klaudia; Dusiel, Julia; Wałachowska, Anna (Quality in Sport, 2025)
Introduction and objective: Athletes practising outdoor sports are particularly exposed to prolonged and intense ultraviolet (UV) radiation, which significantly increases the risk of developing skin cancer, including melanoma and non-melanoma types. Despite growing awareness of these risks, the effectiveness of photoprotection in this population remains insufficient, mainly due to irregular sunscreen use, incorrect application habits, and numerous environmental and organisational barriers. The aim of this review is to present the current state of knowledge on the effectiveness of sun protection methods used by outdoor athletes and to assess their role in skin cancer prevention. Review methods: All data were collected from publicly available sources. This article’s databases were accessed via PubMed, Scopus and Web of Science. A brief description of the state of knowledge: Research shows that athletes often use sun protection incorrectly - applying too little sunscreen, skipping reapplication and inconsistently using physical barriers like UPF clothing or headgear. Long-distance runners, cyclists, skiers and water sports enthusiasts are most exposed to UV radiation. Effective protection is further hampered by intense sweating, reflection of rays from water or snow, sporting pressure and concerns about comfort. Although awareness is growing, it rarely becomes routine. Educational programmes, coach support and technologies such as UV sensors or mobile apps show promising results. Summary: Effective protection requires a multidimensional approach combining education, behavioural support and UV policies in sports settings. Best results come from using both chemical and physical methods, but only when applied regularly and correctly. Technology and stronger involvement of sports organisations can improve adherence. With rising skin cancer rates, sport-specific, practical UV-prevention guidelines are urgently needed.